Beans for breakfast? How exportable is the British workfare model? - Olivier Bargain; Kristian Orsini (University of Essex, Institute for Social and Economic Research (ISER), 2006)
Social assistance and inactivity traps have long been considered as one of the main causes of the poor employment performance of EU countries. The success of New Labour in the UK has triggered a growing interests in instruments capable of combining the promotion of responsibility and self-sufficiency with solidarity with less skilled workers. Making-work-pay (MWP) policies, consisting of transfers to households with low earning capacity, have quickly emerged as the most politically acceptable instruments in tax-benefit reforms of many Anglo-Saxon countries. This chapter explores the impact of introducing the British Working Families' Tax Credit (WFTC) in three EU countries with rather different labor market and welfare institutions: Finland, France and Germany. Simulating the reform reveals that, while first-round effects on income distribution is considerable, the interaction of the new instrument with the structural characteristics of the economy and the population may lead to counterproductive second round effects (i.e. changes in economic behavior). The implementation of the reform, in this case, could only be justified if the social inclusion (i.e. transition into activity) of some specific household types (singles and single mothers) is valued more than a rise in the employment per se.
Keywords: H31; H53; I32; I38; 330; tax-benefit systems; in-work benefits; microsimulation; poverty